2014
DOI: 10.3892/or.2014.3273
|View full text |Cite
|
Sign up to set email alerts
|

Matrine induces the apoptosis of lung cancer cells through downregulation of inhibitor of apoptosis proteins and the Akt signaling pathway

Abstract: Abstract. Lung cancer is the leading cause of cancer-related mortality in humans. The prognosis for advanced lung cancer patients is extremely poor. Current standard care is rather ineffective for prolonging patient life while preserving satisfactory quality of life due to adverse side-effects. Matrine extracted from the traditional Chinese herbal plant Sophora flavescens was shown to induce cancer cell death in vitro. The aim of this study was to investigate the effect of matrine on the proliferation and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…Alkaloids are a group of naturally occurring chemical 140 [114][115][116][117][118][119] pathway and down-regulation of inhibitor of apoptosis proteins (18). Another study reports that matrine inhibits the invasive activities of human osteosarcoma cells through down-regulation of the ERK/NF-κB pathway in intro and in vivo (19).…”
Section: Alkaloidmentioning
confidence: 99%
“…Alkaloids are a group of naturally occurring chemical 140 [114][115][116][117][118][119] pathway and down-regulation of inhibitor of apoptosis proteins (18). Another study reports that matrine inhibits the invasive activities of human osteosarcoma cells through down-regulation of the ERK/NF-κB pathway in intro and in vivo (19).…”
Section: Alkaloidmentioning
confidence: 99%
“…The cells were grown in a humidified incubator at 37 °C and under an atmosphere of 5% CO 2 . Cells were grown on sterile tissue culture petri dishes and passaged once every 2 to 3 days [19,31,32]. …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that matrine targeted numerous cellular proteins, including β-catenin, AKT, and mTOR (18)(19)(20). ERK is also targeted by matrine (21).…”
Section: Discussionmentioning
confidence: 99%